Effects of Fusarium graminearum and Fusarium poae on disease parameters, grain quality and mycotoxins contamination in bread wheat (Part I) - Martínez, Mauro (2020)
BACKGROUND: Wheat is the most important winter crop in the world, being affected by the presence of fungal, mainly those belonging to the Fusarium genus. Fusarium head blight (FHB) is a serious disease that causes important economic damage and quantitative/qualitative losses, with Fusarium graminearum and Fusarium poae being two of the most isolated species worldwide. The present study aimed to evaluate the interaction between F. graminearum and F. poae and the effects on disease parameters, grain quality and mycotoxin contamination on five wheat genotypes under field conditions during three growing seasons. RESULTS: Statistical differences between Fusarium treatments were found for disease parameters, grain quality and mycotoxin contamination during the 2014/2015 growing season. High values of incidence (58.00 ± 8.00%), severity (6.28 ± 1.51%) and FHB index (4.72 ± 1.35) were observed for F. graminearum  + F. poae treatment. Regarding grain quality, the results showed that the degradation of different protein fractions depends on each Fusarium species: glutenins were degraded preferably by F. graminearum (−70.82%), gliadins were degraded preferably by F. poae (−29.42%), whereas both protein fractions were degraded when both Fusarium species were present (−60.91% and −16.51%, respectively). Significant differences were observed for mycotoxin contamination between genotypes, with Proteo being the most affected (DON = 12.01 ± 3.67 μg g−1). In addition, we report that 3‐ADON predominated over 15‐ADON in the three seasons evaluated. CONCLUSION: Variations in plant–pathogen interaction (Fusarium– wheat pathosystem) should be considered at least in years with favorable climatic conditions for FHB development, as a result of the potential impact of this disease on grain quality and mycotoxin contamination.